A Combination of Nevus and Papilloma in the Same Lesion in the Conjunctiva - GEÇER, Melin; GEÇER, MELİN; Sahan, Berna; Ciftci, Ferda (My University, 2018)
A 28-year-old female patient was admitted to our clink with a mass in the caruncle of her left eye. As per a slit-lamp examination, a red-pink pedicle mass was hanging out of the pigmented base. The mass size was 10 mm, and it contained lobular structures. An excisional biopsy was performed. Histopathologically, the papillary proliferation of squamous epithelia on the conjunctiva was detected, and the epitheliumshowed koilocyte-like cells. Pigmented nevoid cells were seen on the basal layer of the epidermis and subepithelial zone. Immunohistochemistry tests were performed to investigate the effect of human papilloma virus (HPV), but HPV dye staining was not observed. Lower in-situ hybridization of the HPV text was studied. It was accepted as negative because of a non-specific and weak signal monitoring. Finally, the mass was reported as conjunctival nevus and squamous papilloma within the same lesion. No recurrence was observed at a 2-year follow-up. Despite the fact that the conjunctival nevi and papilloma often separately appear, they were simultaneously seen in the same lesion in this case, which is very rare. To the best of our knowledge, this is the first case report in the literature wherein the conjunctival nevi and papilloma are simultaneously seen in the same lesion.